Weed resistance to herbicides - Vrbničanin, Sava (Acta herbologica, 2021)
Weed resistance to herbicides represents the acquired resistance of individuals to complete the life cycle and leave offspring in the conditions of their longer exposure to the same herbicide, ie herbicides of the same mechanism of action to which they were sensitive at the beginning of application. According the herbicide resistance mechanisms all processes can be grouped as follows: target-site resistance, non-target-site resistance, cross-resistance and multiple-resistance. Currently herbicide resistance has been reported in 514 cases (species x site of action) in the world, in 262 weed species (152 dicotyledons, 110 monocotyledons). Many of those biotypes are resistant to ALS inhibitors, PS II inhibitors, EPSPS inhibitors and ACC-ase inhibitors. The higher number of resistance to ALS inhibitors has been confirmed in the next weed species: Amaranthus retroflexus, Sorghum halepense, Ambrosia artemisiifolia and Helianthus annuus.